Antiplasmodial and Haem Transition Activities of Tannin and Glycoside Fractions of Phyllanthus amarus - Blessed, Akpor Ugochukwu (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Malaria remains a major public health threat, particularly in Nigeria, amid rising resistance of Plasmodium falciparum to existing therapies, underscoring the need for new, effective, and affordable antimalarials. This study aimed to evaluate the antiplasmodial activity of Phyllanthus amarus tannin and glycoside extracts and to assess their effects on haem-related mechanisms. Standard procedures were used to prepare crude extracts, which were tested against sensitive P. falciparum 3D7 strains; parasite growth inhibition and haem transition inhibition assays were conducted, and performance was benchmarked against chloroquine. Key findings show that the tannin extract reduced parasite growth (albeit less than chloroquine, p < 0.05) with IC₅₀ = 3.09 µg/mL, whereas the glycoside extract exhibited minimal activity (IC₅₀ = 14.45 µg/mL) compared with chloroquine (IC₅₀ = 0.41 µg/mL). Neither extract significantly inhibited haem transition, in contrast to chloroquine, suggesting possible interference at early stages of haem oligomerisation while haem remains in solution. The study concludes that the tannin extract demonstrates promising antiplasmodial activity, while the glycoside extract does not. The contribution and implication are that the antimalarial properties of P. amarus observed in vitro and in vivo may be partly attributable to its tannin content, warranting further investigation as a candidate for antimalarial development.